STUDI PENGOLAHAN KRIPIK TEMPE GEMBUS DALAM MENDONGKRAK EKONOMI DESA KARANGANYAR DUSUN NGADIWINATAN II - Farkhana Amaliyah; Dian Amelia (UIN Sunan Kalijaga, 2022)
Ngadiwinatan II is a part of the Karanganyar tourist village in Borobudur District, Magelang Regency which has the potential for a cottage industry to make tofu. Production conditions that are still not able to boost the community's economy are the background of this research. The purpose of this study was to develop a new product in the form of tempe gembus chips to optimize the value and selling price of tofu dregs. In more detail, this study analyzed the proportion of tempe gembus ingredients in the form of rice flour, tapioca flour with tofu waste to produce the best quality. This research applies both obsevational and experimental method. The results showed that the proportion of tofu dregs: tapioca flour = 66.6%: 33.3% was the best treatment to get a crispy and delicious tempeh gembus product.